Financing Prosperity by Dealing with Debt - Harker, Christopher; Horton, Amy (Global Prosperity in Thought and Practice, 2022)
In an era when many of us depend on debt to survive but struggle with its consequences, Financing Prosperity by Dealing with Debt draws together current thinking on how to solve debt crises and promote prosperity. By profiling existing action by credit unions and community organisations, alongside bold proposals for the future, with contributions from artists, activists and academics, the book shows how we can rethink the validity and inevitability of many contemporary forms of debt through organising debt audits, promoting debt cancellation and expanding member-owned co-operatives. The authors set out legal and political methods for changing the rules of the system to provide debt relief and reshape economies for more inclusive and sustainable flourishing. The book also profiles community-based actions that are changing the role of debt in economic, social and political life - among them, participatory art projects, radical advice networks and ways of financing feminist green transition. While much of the research and activism documented here has taken place in London, the contributors show how different initiatives draw from and generate inspiration elsewhere, from debt audits across the global south, creative interventions around the UK and grassroots movements in North America. Financing Prosperity by Dealing with Debt moves beyond critique to present a wealth of concrete ways to tackle debt and forge the prosperous communities we want for the future.